Implementasi Total Productive Maintenance Pada UD. Palapa Kabupaten Nganjuk - Sari, Natasya Amelia Kumala; Buniarto, Edwin Agus; Mutaqien, Zaenul (Innovative: Journal Of Social Science Research, 2025)
This study aims to implement Total Productive Maintenance at UD. Palapa to improve production efficiency and reduce machine downtime. The main problem faced is the high downtime of production machines, which disrupts the production process, decreases production capacity, and increases operational costs. The research method used is a qualitative method with a descriptive approach. Data were obtained through direct observation, interviews with operators and management, and analysis of company documents related to machine maintenance schedules and downtime data. The analysis was carried out based on the TPM concept with a focus on three main pillars, namely autonomous maintenance, planned maintenance, and training and education. The results of the study showed that the maintenance system implemented at UD. Palapa is still reactive, with maintenance only carried out after damage occurs. Operator participation in maintenance is still minimal, which has an impact on the low Overall Equipment Effectiveness value of 71%, far below the industry standard of 85%. Therefore, effective TPM implementation is expected to increase machine availability, reduce downtime, and increase productivity and product quality. As a recommendation, the implementation of TPM should be carried out in stages, starting with autonomous maintenance by operators, periodic training to improve operator understanding, and the implementation of planned maintenance schedules. Proper implementation will help UD. Palapa improve competitiveness and achieve higher production efficiency